2012
DOI: 10.1210/jc.2011-3180
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian Hormone Is a Marker of Gonadotoxicity in Pre- and Postpubertal Girls Treated for Cancer: A Prospective Study

Abstract: AMH is detectable in girls of all ages and falls rapidly during cancer treatment in both prepubertal and pubertal girls. Both the fall during treatment and recovery thereafter varied with risk of gonadotoxicity. AMH is therefore a clinically useful marker of damage to the ovarian reserve in girls receiving treatment for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(128 citation statements)
references
References 36 publications
(44 reference statements)
8
108
0
7
Order By: Relevance
“…In the pivotal study by Anderson et al [41], AMH serum levels rapidly and markedly fell after the first cycles of CT and during the treatment, becoming undetectable in many patients. AMH serum levels may even increase again over time, but return to pre-CT levels appeared unlikely [37,[47][48][49]. In large casecontrol studies, BC survivors who underwent CT had lower AMH serum levels than age-matched controls [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In the pivotal study by Anderson et al [41], AMH serum levels rapidly and markedly fell after the first cycles of CT and during the treatment, becoming undetectable in many patients. AMH serum levels may even increase again over time, but return to pre-CT levels appeared unlikely [37,[47][48][49]. In large casecontrol studies, BC survivors who underwent CT had lower AMH serum levels than age-matched controls [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that AMH was detectable in girls of all ages but decreased progressively during chemotherapy in both preand post-pubertal girls, eventually becoming undetectable in 50% of patients. AMH levels showed no recovery in the high-risk group, while there was a recovery in the low/medium risk group after the completion of chemotherapy (Brougham et al 2012). Interestingly, authors observed that AMH, due to the physiological quiescence of the hypothalamic-pituitary-gonadal axis at this age, was the only reliable biomarker for ovarian damage evaluation in prepubertal children (Brougham et al 2012).…”
Section: Amh and Chemo-induced Gonadal Damage In Cancer Patientsmentioning
confidence: 99%
“…Furthermore, they showed that high pretreatment AMH levels were predictive of higher AMH levels during recovery of ovarian function after chemotherapy (Rosendahl et al 2010). Brougham et al (2012) prospectively evaluated AMH levels in children as a marker of ovarian reserve during cancer treatment. A total of 22 patients with a median age of 4.4 years were enrolled before initiation of cancer treatment.…”
Section: Amh and Chemo-induced Gonadal Damage In Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimül-lerian hormone is detectable at all ages and, unlike fsh, is stable throughout the menstrual cycle; it can therefore be assessed at the time of presentation. In combination with the patient's age, amh can help to assess future fertility by quantifying the short-term chemotoxic effects on ovarian reserve 59 , providing an estimated age of menopause 60,61 and assessing the patient's susceptibility to the gonadotoxic effects of chemotherapy 62,63 .…”
Section: Assessment Of the Young Cancer Patientmentioning
confidence: 99%